Preterm delivery after fetoscopic laser surgery for twin–twin transfusion syndrome: etiology and risk factors. (May 2017) - Malshe, A.; Snowise, S.; Mann, L. K.; Boring, N.; Johnson, A.; Bebbington, M. W.; Moise, K. J.; Papanna, R.
ABSTRACT: Objective: Preterm delivery after fetoscopic laser surgery (FLS) for twin–twin transfusion syndrome (TTTS) is a major complication. The causative factors leading to preterm delivery continue to be elusive and a better understanding of the risk factors could reduce complications. The objective of this study was to determine the etiology of preterm delivery after FLS for TTTS and its associated risk factors. Methods: This was a secondary analysis of a prospective study of 203 patients with TTTS who underwent FLS at a single center between September 2011 and December 2014. Preoperative, operative, postoperative, delivery and neonatal data were reviewed. Preterm delivery was categorized according to etiology into three groups: spontaneous (SPT), indicated (IND) and elective (ELC). Comparisons between groups were performed by ANOVA. Kaplan–Meier survival analysis was performed to compare the procedure‐to‐delivery interval between groups. To identify risk factors for preterm delivery, logistic regression, with calculation of relative risks (RR), was performed, with P  < 0.05 considered statistically significant. Results: Mean gestational age at time of FLS was 20.6 ± 2.4 weeks and mean gestational age at delivery was 30.9 ± 4.7 weeks. Iatrogenic preterm prelabor rupture of membranes (iPPROM) occurred in 39% of cases. SPT preterm delivery occurred in 97 (48%) patients, IND preterm delivery in 65 (32%) and ELC preterm delivery in 41 (20%). In the IND group, 30 (46%) patients delivered for fetal indications, 31 (48%) for maternal indications and four (6%) for combined fetal and maternal indications. The overall chorioamnionitis rate was 6.4%; of these, nine (9%) were in the SPT group and four (6%) were in the IND group, with no case occurring in the ELC group. There was a significant difference in procedure‐to‐delivery interval between groups ( P  < 0.0001). Using variables from the ELC group as a baseline, significant risk factors for SPT preterm delivery were iPPROM (RR, 16.2 (95% CI, 4.5–57.7)), preoperative cervical length (RR, 0.96 (95% CI, 0.92–0.998)) and number of anastomoses (RR, 1.14 (95% CI, 1.02–1.27)). Significant risk factors for IND preterm delivery were iPPROM (RR, 9.6 (95% CI, 2.6–35.0)) and number of ablated anastomoses (RR, 1.13 (95% CI, 1.02–1.30)). Conclusion: iPPROM and an increased number of ablated placental anastomoses were associated independently with SPT and IND preterm deliveries. A shorter preoperative cervical length was associated with SPT preterm delivery. Strategies to prevent iPPROM and for management of cervical length shortening are needed urgently in these pregnancies. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.